Analysis of Near-wall Coherent Structure of Spiral Flow in Circular Pipe Based on Large Eddy Simulation - Z. Wang; Y. Yin; S. Li; Y. Xu; L. Li; G. Li (Journal of Applied Fluid Mechanics, 2023)
Based on the large eddy simulation method, this study performed the three-dimensional transient numerical analysis of the near-wall flow field of the spiral flow in a circular pipe and applied the sub-grid model of the kinetic energy transport. The low-speed bands, streamwise vortices and hairpin vortices of the spiral flow in the near-wall region of the circular pipe are determined using the Q criterion. The ejection and sweeping of coherent structures are identified using the velocity vector of the near-wall region; moreover, the two methods of creating the hairpin vortices are established by the image time series. The results demonstrate that the development directions of the near-wall bands, streamwise vortices and hairpin vortices of the spiral flow in the circular pipe develop along the path of the spiral line. The average spanwise period of the low-speed bands in the near-wall region is approximately 120 wall units, the length is more than 900 wall units and the height is not more than 40 wall units. The separation distance of the streamwise vortices is about 119 wall units. It has a certain angle with the wall (approximately 22°). The average burst period of a hairpin vortices is less than 0.015 s.